IDENTIFYING THE THERMAL PARAMETERS OF DIESEL ENGINE USING DIESEL FUEL AND SOYBEAN METHYL ESTER BLENDS - Wisam Al-Obaidi; Ahmed M. Hassan; Husam Kareem Mohsin Al-Jothery; Dhafer A. Hamzah (Journals Park Publishing, 2025)
This work examines numerically the use of soybean methyl ester (SME) biodiesel along with diesel in a constant-speed, single-cylinder diesel engine. Two fuels were tested: 20%SME and pure SME, besides a baseline neat diesel for comparison. The simulation software Diesel-RK was used in this study, which is based on the multizone combustion model. The results obtained for selected biodiesel showed a quicker start of combustion due to the reduction in the delay period, which is impacted by cetane number. Compared to diesel, the SMD was increased by 8.7% and 24% for the use of 20% SME and SME, respectively. The brake thermal efficiency (BTE) was decreased by 0.8% for 20%SME while it decreased by 6.62% with the use of pure SME. Remarkable reduction in the nitrogen oxides (NOx) emissions was reported with the use of SME by 50% compared to diesel fuel. The carbon dioxide (CO2) emissions were increased as a result of using SME blends with diesel. The comparison between obtained findings with the result of other studies reported an accepted deviation.
Keywords: SME Biodiesel; Combustion; Diesel-Rk software; NOx; Pollutant emissions.